Analisis Perkembangan Kinerja Keuangan Perusahaan - Abdullah, Julie; Hasanuddin, Hasanuddin; Lamuda, Ilyas; Uno, Rahmat (Gorontalo Accounting Journal, 2024)
This study analyzes the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during and after the Covid-19 pandemic. Using activity, profitability, and liquidity ratios, the results show that most companies experienced financial performance fluctuations. Activity and profitability ratios remained below industry standards, while liquidity ratios varied, with some companies maintaining their ability to meet short-term obligations. This study highlights the need for improved operational efficiency and financial strategies to achieve optimal performance.